2021
DOI: 10.1002/biof.1704
|View full text |Cite
|
Sign up to set email alerts
|

BCL‐6 promotes the methylation of miR‐34a by recruiting EZH2 and upregulating CTRP9 to protect ischemic myocardial injury

Abstract: Acute myocardial infarction (AMI) and the following heart failure are public health problems faced all over the globe. The current study set out to investigate the role of B-cell lymphoma 6 (BCL-6) in cardiac protection after AMI.Initially, AMI mouse models and H9c2 cell oxygen-glucose deprivation (OGD) models were established. The cell models were transfected with the vectors containing oe-BCL-6, oe-EZH2, sh-EZH2, miR-34a mimic, and miR-34a inhibitor. RT-qPCR and Western blot analysis were applied to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In this regard, a recent study demonstrated that miR-34a was highly expressed in the heart tissue of AMI, which promoted cell apoptosis and oxidative stress. The results indicated that inhibition of miR-34a attenuated myocardial injury by multiple gene regulation of cellular phenotypes (69). Recent studies have shown that some mature miRs are also modified by m6A/m5C methylation, and that these modified mature miRs are significantly differentially expressed among cancer tissues (70).…”
Section: Roles Of Mir-34a In MI and Hfmentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, a recent study demonstrated that miR-34a was highly expressed in the heart tissue of AMI, which promoted cell apoptosis and oxidative stress. The results indicated that inhibition of miR-34a attenuated myocardial injury by multiple gene regulation of cellular phenotypes (69). Recent studies have shown that some mature miRs are also modified by m6A/m5C methylation, and that these modified mature miRs are significantly differentially expressed among cancer tissues (70).…”
Section: Roles Of Mir-34a In MI and Hfmentioning
confidence: 98%
“…Recent studies have shown that some mature miRs are also modified by m6A/m5C methylation, and that these modified mature miRs are significantly differentially expressed among cancer tissues (70). Similarly in the cardiovascular system, methylation of miR-34a promoted by Bcl-6 has a cardioprotective effect on AMI via the EZH2/miR-34a/CTRP9 axis (69). In the early stage of AMI, prevention of heart failure and left ventricular remodeling are closely related to the prognosis of patients, and left ventricular remodeling after AMI is associated with poor prognosis (68).…”
Section: Roles Of Mir-34a In MI and Hfmentioning
confidence: 99%
“…The lncRNA NEAT1 recruits EZH2 to the Smad7 promoter, increases Smad7 methylation, and accelerates the development of heart failure and ventricular remodeling [ 175 ]. Also, EZH2 can promote the methylation level of mir-34a to inhibit the apoptosis of cardiomyocytes after acute myocardial infarction and improve myocardial injury [ 176 ]. In addition, lncRNA ANRIL is upregulated in patients with coronary atherosclerotic heart disease and promotes the binding of WDR5 (the key subunit of the HMT H3K4MT complex) to HDAC3 to form the WRD5–HDAC3 complex, which regulates oxidative stress and increases reactive oxygen species (ROS) levels [ 177 ].…”
Section: Regulatory Mechanisms Of Chromatin Modifiersmentioning
confidence: 99%
“…15 In addition, BCL6 may play an important role in the pathophysiological process of ischemiahypoxic injury in cardiomyocytes and protect cardiomyocytes by inhibiting oxidative stress, inflammation, and cell apoptosis. 16,33,34 However, the regulatory mechanisms of BCL6 in cardiomyocytes are not fully understood. In this study, using the mouse heart failure model and the cardiomyocyte injury model, DDX17 was found to bind to BCL6 and jointly participate in inhibiting the expression of the downstream gene Drp1, which results in blocking the excessive fission of myocardial mitochondria and maintaining their homeostasis and function.…”
Section: Overexpression Of Ddx17 In Cardiomyocytes Reduces Myocardial...mentioning
confidence: 99%